Extensive sensorimotor training enhances nociceptive cortical responses in healthy individuals. (1st December 2022) - Zamorano, Anna M.; Kleber, Boris; Arguissain, Federico; Vuust, Peter; Flor, Herta; Graven‐Nielsen, Thomas
Abstract: Background: Prolonged and repeated sensorimotor training is a crucial driver for promoting use‐dependent plasticity, but also a main risk factor for developing musculoskeletal pain syndromes, yet the neural underpinnings that link repetitive movements to abnormal pain processing are unknown. Methods: Twenty healthy musicians, one of the best in vivo models to study use‐dependent plasticity, and 20 healthy non‐musicians were recruited. Perceptual thresholds, reaction times (RTs) and event‐related potentials (ERPs) were recorded using nociceptive intra‐epidermal and non‐nociceptive transcutaneous electrical stimulation. Results: In response to comparable stimulus intensities, musicians compared to non‐musicians showed larger non‐nociceptive N140 (associated with higher activation of regions within the salience network), higher nociceptive N200 ERPs (associated with higher activation of regions within the sensorimotor network) and faster RTs to both stimuli. Non‐musicians showed larger non‐nociceptive P200 ERP. Notably, a similar P200 component prominently emerged during nociceptive stimulation in non‐musicians. Across participants, larger N140 and N200 ERPs were associated with RTs, whereas the amount of daily practice in musicians explained non‐nociceptive P200 and nociceptive P300 ERPs. Conclusions: These novel findings indicate that the mechanisms by which extensive sensorimotor training promotes use‐dependent plasticity in multisensory neural structures may also shape the neural signatures of nociceptive processing in healthy individuals. Significance: Repetitive sensorimotor training may increase the responsiveness of nociceptive evoked potentials. These novel data highlight the importance of repetitive sensorimotor practice as a contributing factor to the interindividual variability of nociceptive‐related potentials.